2012
DOI: 10.1177/0892705711429981
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of coconut shell powder filled polylactic acid biocomposites

Abstract: The acrylic acid was used as chemical modifier to improve the properties of coconut shell powder (CSP) filled polylactic acid (PLA) biocomposites. The effects of filler content and acrylic acid on tensile properties, thermal properties, and morphology of PLA/CSP biocomposites were investigated. It was found that the addition of CSP to PLA biocomposites have decreased the tensile strength and elongation at break, however the modulus of elasticity increased. The treated PLA/CSP biocomposites with acrylic acid ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 25 publications
4
66
0
Order By: Relevance
“…Previous studies have shown that the PLA matrix demonstrates good mechanical behavior; however, PLA alone is not sufficient to produce a favorable product (Lee and Wang 2006). Formerly, PLA composites improved the properties of composites through blends with low cost, renewable, and fully biodegradable natural fillers, such as wood flour, starch, lignocellulosic fibers/fillers, and natural cellulose fibers (Oksman et al 2003;Masud et al 2005;Anuar 2007;Salmah et al 2012). PLA has the advantage of being both renewable and biodegradable, since lactic acid is produced from biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the PLA matrix demonstrates good mechanical behavior; however, PLA alone is not sufficient to produce a favorable product (Lee and Wang 2006). Formerly, PLA composites improved the properties of composites through blends with low cost, renewable, and fully biodegradable natural fillers, such as wood flour, starch, lignocellulosic fibers/fillers, and natural cellulose fibers (Oksman et al 2003;Masud et al 2005;Anuar 2007;Salmah et al 2012). PLA has the advantage of being both renewable and biodegradable, since lactic acid is produced from biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers are more interested in the utilization of agricultural wastes such as corn cob , palm kennel shell (Salmah et al 2013), coconut shell (Chun et al 2012;Salmah et al 2012b), and chitosan (Salmah and Azieyanti 2011; to produce biocomposites that reduce cost as well as enhance the properties and biodegradability of biocomposites. Corn (Zea mays) is a biomass resource that is cultivated around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The result found the fiber content increased, the elongation at break of PLA/DHF biocomposite decreased. In general, natural fiber is rigid material that not elongate much [18]. Thus, the addition of DHF would not contribute on the elongation of PLA matrix.…”
Section: Tensile Propertiesmentioning
confidence: 99%